A randomized double blind placebo-control trial on safety and efficacy of Viva QS for smoking cessation in Malaysian adult population - Mohamad Noor, Zaswiza; Nik Mohamed, Mohamad Haniki; Md Aris, Mohd Aznan; Draman, Samsul; Shaik Rahman Bux, Siti Halimah Bux; Abd Rahman, Norny Syafinaz (2009)
Introduction: Nicotine dependence is a life threatening disorder and efforts have been focused to identify new mechanisms to assist smokers to quit. The need to find new interventions is vital. The use of herbals as alternative to current treatments is limited and most studies were without randomized control trial (RCT). To our knowledge, this is the first study in Malaysia using RCT to study herbal medication for smoking cessation. Viva® was introduced in Malaysia to help drug addicts managed withdrawal symptoms. Distaste for cigarettes were noticed in patients undergoing treatment - which led to development of Viva QS® for smoking cessation. Objectives: The objectives of the study were to determine the effectiveness and safety of Viva QS® for quit smoking using randomized double blind placebo-control trial. Method: We conducted mobile smoking cessation programmes (MSCP) to recruit subjects. We reached smokers at workplaces and recruited those attended smoking cessation talks, fulfilled the eligible criteria and agreed to give consent. Demographic and smoking history information, modified Fagerström test score and carbon monoxide level were obtained at baseline. Subjects were randomly assigned to either Viva QS® or placebo groups. Follow-ups were undertaken by phone call and/or face-to-face meeting. Study medication was consumed for six months. Results: Biochemically verified 7-days point prevalence abstinence at week 24 showed significant difference in quit rates between both groups (Viva QS®, 30.7%; placebo, 13.9%; P = 0.015). Significant differences in quit rates between groups were showed in 7-days point prevalence abstinence at week 4 (Viva QS®, 42.7%; placebo, 26.2%; P = 0.038) and week 12 (Viva QS®, 32.0%; placebo, 16.7%; P = 0.031). Adverse events reported showed no difference in both groups with all mean less than 0.065 (slight effects). Conclusions: We suggested Viva QS® as safe and effective for smoking cessation. Further studies should be undertaken in different population samples to assess the effectiveness and safety of the medication to strengthen our findings. Keywords: Safety, Efficacy, herbal, smoking cessation, pharmacotherapy, counselling.